Gene expression profiling following maternal deprivation: Involvement of the brain renin-angiotensin system - Liebl, Claudia; Panhuysen, Markus; Pütz, Benno; Trümbach, Dietrich; Wurst, Wolfgang; Deussing, Jan M.; Mueller, Marianne; Schmidt, Mathias (Frontiers in Molecular Neuroscience, 2009)
The postnatal development of the mouse is characterized by a stress hyporesponsive period (SHRP), where basal corticosterone levels are low and responsiveness to mild stressors is reduced. Maternal separation is able to disrupt the SHRP and is widely used to model early trauma. In this study we aimed at identifying of brain systems involved in acute and possible long-term effects of maternal separation. We conducted a microarray-based gene expression analysis in the hypothalamic paraventricular nucleus after maternal separation, which revealed 52 differentially regulated genes compared to undisturbed controls, among them are 37 up-regulated and 15 down-regulated genes. One of the prominently up-regulated genes, angiotensinogen, was validated using in-situ hybridization. Angiotensinogen is the precursor of angiotensin II, the main effector of the brain renin-angiotensin system (RAS), which is known to be involved in stress system modulation in adult animals. Using the selective angiotensin type I receptor (AT(1)) antagonist candesartan we found strong effects on CRH and GR mRNA expression in the brain a nd ACTH release following maternal separation. AT(1) receptor blockade appears to enhance central effects of maternal separation in the neonate, suggesting a suppressing function of brain RAS during the SHRP. Taken together, our results illustrate the molecular adaptations that occur in the paraventricular nucleus following maternal separation and contribute to identifying signaling cascades that control stress system activity in the neonate.